2019
DOI: 10.1016/j.jacr.2019.02.018
|View full text |Cite
|
Sign up to set email alerts
|

ACR Appropriateness Criteria® Scoliosis-Child

Abstract: Scoliosis is frequently encountered in childhood, with prevalence of 2%. The majority is idiopathic, without vertebral segmentation anomaly, dysraphism, neuromuscular abnormality, skeletal dysplasia, tumor, or infection. As a complement to clinical assessment, radiography is the primary imaging modality used to classify scoliosis and subsequently monitor its progression and response to treatment. MRI is utilized selectively to assess for neural axis abnormalities in those at higher risk, including those with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Recently, the American College of Radiology published their Appropriateness Criteria guidelines to help clinicians define the most appropriate risk factors that could identify an underlying pathology in AIS patients [20]. In their study, patients with the left thoracic curve, short segment curve, hyperkyphosis, rapid curve progression, focal neurologic findings, male sex, pes cavus and functionally disruptive pain were recommended to undergo MRI screening for further evaluation [20]. In 2020, Ramirez et al published a case series study where they demonstrated that one out of three painful AIS patients would have an underlying pathology [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the American College of Radiology published their Appropriateness Criteria guidelines to help clinicians define the most appropriate risk factors that could identify an underlying pathology in AIS patients [20]. In their study, patients with the left thoracic curve, short segment curve, hyperkyphosis, rapid curve progression, focal neurologic findings, male sex, pes cavus and functionally disruptive pain were recommended to undergo MRI screening for further evaluation [20]. In 2020, Ramirez et al published a case series study where they demonstrated that one out of three painful AIS patients would have an underlying pathology [3].…”
Section: Discussionmentioning
confidence: 99%
“…The goal of these studies was to elaborate on a screening protocol that could minimize the use of extensive diagnostic workup in this population. Recently, the American College of Radiology published their Appropriateness Criteria guidelines to help clinicians define the most appropriate risk factors that could identify an underlying pathology in AIS patients [20]. In their study, patients with the left thoracic curve, short segment curve, hyperkyphosis, rapid curve progression, focal neurologic findings, male sex, pes cavus and functionally disruptive pain were recommended to undergo MRI screening for further evaluation [20].…”
Section: Discussionmentioning
confidence: 99%
“…Radiography is usually the first imaging method to study congenital vertebral anomalies and related deformities, allowing their classification, evaluation of severity, risk of deformity progression, and vertebral count (15). As the number of bone malformations increases, there is a higher incidence of cord anomalies ranging from 20% to 58% (9,15,16), being higher in the presence of combined failures of segmentation and formation.…”
Section: Ct and Mri In Congenital Conditions Of The Spinementioning
confidence: 99%
“…Radiography is usually the first imaging method to study congenital vertebral abnormalities and related deformities, allowing their classification, evaluation of severity and assessment of risk of progression (16). As the number of bony malformations increases, there is a higher incidence of cord anomalies ranging from 20% to 58% (16)(17)(18) and being greater in the presence of combined failures of segmentation and formation (18). MRI is the appropriate technique for complete evaluation of intraspinal abnormalities.…”
Section: Congenital Pathologymentioning
confidence: 99%